Perbandingan Kinerja Keuangan Perbankan Sebelum dan Sesudah Akuisisi di Bursa Efek Indonesia - Ni Kadek Gita Cahyani; I Gst. Bgs. Wiksuana (Public Service and Governance Journal, 2024)
Financial performance reflects the quality of the company may be at risk. The pandemic has resulted in various sectors, including a decline in profits. The acquisition business development strategy is used to survive in a condition. Acquisition is the process of taking over ownership resulting in the transfer of control. The research objective analyzes the differences in banking financial performance before and after being acquired by the acquiring company. Financial performance is observed from liquidity with current ratio, solvency measured debt to total asset ratio, profitability measured return on assets, activity measured total asset turnover, and market measured earnings per share. Data after being collected is processed descriptive statistics and normality tests so as to find normally distributed data will be tested through paired sample t-test while data that is not normally distributed is tested by the Wilcoxon signed rank method. The average descriptive statistical results after experiencing an increase in performance. The results of hypothesis testing show that there is a difference in significant improvement in liquidity and activity ratios, there is a significant decrease in solvency, while based on profitability and market there is no significant improvement. Overall the results show that the acquired banks have not fully achieved synergy, the company must review economic conditions when planning development strategies in order to achieve synergy.